Classification of Common Partial Discharge Types in Oil-Paper Insulation Using Acoustic Signals - Harbaji, Mustafa (2014)
A Master of Science thesis in Electrical Engineering by Mustafa Harbaji entitled, "Classification of Common Partial Discharge Types in Oil-Paper Insulation Using Acoustic Signals," submitted in February 2014. Thesis advisor is Dr. Ayman Hassan El-Hag and thesis co-advisor Dr. Khaled Bashir Shaban. Available are both soft and hard copies of the thesis.